Authenticity and Experience Quality Effect Customer Loyalty of Thematic Restaurants and Demography as Moderation - Ananda Sabil Hussein; Reni Rupianti; Norma Khairunisa; Khaula Fathia Humaira (Profesional Muda Cendekia Publishing, 2022)
An increase in activity in the culinary sector provides an opportunity for gastronomic tourism to rise and develop. Gaining tourist loyalty through the success of creating unique experiences is a source of competitive advantage for each destination. This study aimed to examine the mediating effect of perceived authenticity on the relation between experience quality and customer loyalty. This research was conducted in ethnic restaurants spread across East Java and used 200 samples of gastronomic tourists analyzed by SEM-PLS. This study explained that food quality and physical environment had a significant effect on customer loyalty. Service quality had a significant effect on perceived authenticity. Perceived authenticity had a significant effect on customer loyalty. Perceived authenticity is a full mediation of the relation between service quality and customer loyalty. Meanwhile, in the moderation test, demography was not able to moderate the relation between experience quality and customer loyalty.